2019
DOI: 10.1186/s12943-019-1046-7
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circRHOT1 promotes hepatocellular carcinoma progression by initiation of NR2F6 expression

Abstract: Background Increasing evidence has revealed a close relationship between non-coding RNAs and cancer progression. Circular RNAs (circRNAs), a recently identified new member of non-coding RNAs, are demonstrated to participate in diverse biological processes, such as development, homeostatic maintenance and pathological responses. The functions of circRNAs in cancer have drawn wide attention recently. Until now, the expression patterns and roles of circRNAs in hepatocellular carcinoma (HCC) have rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
218
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(220 citation statements)
references
References 43 publications
2
218
0
Order By: Relevance
“…Circ-ACC1 has been demonstrated to directly bind to AMPK β and Îł subunits and facilitate AMPK holoenzyme assembly, stability, and activity [48]. CircRHOT1 was found to promote hepatocellular carcinoma (HCC) growth through the recruitment of TIP60 to the promoter of NR2F6 and initiating NR2F6 transcription [49]. A study reported that circZKSCAN1 physically bound an RBP FMRP against CCAR1 complex and inhibited HCC [50].…”
Section: Discussionmentioning
confidence: 99%
“…Circ-ACC1 has been demonstrated to directly bind to AMPK β and Îł subunits and facilitate AMPK holoenzyme assembly, stability, and activity [48]. CircRHOT1 was found to promote hepatocellular carcinoma (HCC) growth through the recruitment of TIP60 to the promoter of NR2F6 and initiating NR2F6 transcription [49]. A study reported that circZKSCAN1 physically bound an RBP FMRP against CCAR1 complex and inhibited HCC [50].…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the ability of Cas13d to identify and credential bona-fide essential circRNAs, we next sought to use our optimized Cas13d system to target previously reported essential circRNAs. For instance, circRHOT1 knockout by depleting flanking CSs suppressed HCC's cell proliferation 21 . To determine if Cas13d can validate the essentiality of circRHOT1 in HCC cells, we silenced its expression in two HCC cell lines, Huh7 and PLC/PRF/5 cells ( Fig.…”
mentioning
confidence: 99%
“…Further, circRHOT1 promotes proliferation and invasion of pancreatic cancer cells [16]. In HCC, circRHOT1 is significantly upregulated and initiate NR2F6 expression to promote turmor progression, the expression of circRHOT1 was related to patient prognosis [15]. CircRNAs have been regarded as regulators or biological markers in many types of diseases, including pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…hsa_circ_0005397 is derived from the RHOT1gene and has been termed circRHOT1.The circRHOT1 expression was related to the pancreatic cancer cell proliferation, invasion and migration [15].…”
Section: Introductionmentioning
confidence: 99%